Sosialisasi Standar Akuntansi Keuangan Entitas Privat (SAK EP) untuk Meningkatkan Pengetahuan Calon Akuntan Mahasiswa STIE Semarang - Ratna Herawati; Agung Prajanto; Dian Indriana Hapsari (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2026)
Financial Accounting Standards (SAK) in Indonesia continuously evolve in step with developments in the business world, the global economy, and international accounting standards. The Financial Accounting Standard for Private Entities (SAK EP) was ratified by the Financial Accounting Standards Board (DSAK) to replace the Financial Accounting Standard for Entities Without Public Accountability (SAK ETAP) as part of the evolution of financial accounting standards. Aspiring accountants—such as accounting students preparing to become entry-level auditors—need to understand SAK EP, as it serves as a primary guideline for conducting evaluations. A community service team from the Faculty of Economics and Business at Dian Nuswantoro University conducted an outreach program to introduce this new standard to aspiring auditors—specifically students from STIE Semarang—aiming to provide them with an overview of SAK EP. The material was presented using a combination of lectures, Q&A sessions, and discussions. Participants engaged well with the program, demonstrating enthusiasm and a positive response. The increased understanding of SAK EP among the STIE Semarang students indicates that the program successfully achieved its objectives, and it is hoped that similar initiatives will continue in the future.